Parallel pathways of seizure generalization - Dabrowska, Natalia (Brain, 2019)
Generalized convulsive status epilepticus is a life-threatening emergency, because recurrent convulsions can cause death or injury. A common form of generalized convulsive status epilepticus is of focal onset. The neuronal circuits activated during seizure spread from the hippocampus, a frequent site of seizure origin, to the bilateral motor cortex, which mediates convulsive seizures, have not been delineated. Status epilepticus was initiated by electrical stimulation of the hippocampus. Neurons transiently activated during seizures were labelled with tdTomato and then imaged following brain slice clearing. Hippocampus was active throughout the episode of status epilepticus. Neuronal activation was observed in hippocampus parahippocampal structures: subiculum, entorhinal cortex and perirhinal cortex, septum, and olfactory system in the initial phase status epilepticus. The tdTomato-labelled neurons occupied larger volumes of the brain as seizures progressed and at the peak of status epilepticus, motor and somatosensory cortex, retrosplenial cortex, and insular cortex also contained tdTomato-labelled neurons. In addition, motor thalamic nuclei such as anterior and ventromedial, midline, reticular, and posterior thalamic nuclei were also activated. Furthermore, circuits proposed to be crucial for systems consolidation of memory: entorhinal cortex, retrosplenial cortex, cingulate gyrus, midline thalamic nuclei and prefrontal cortex were intensely active during periods of generalized tonic-clonic seizures. As the episode of status epilepticus waned, smaller volume of brain was activated. These studies suggested that seizure spread could have occurred via canonical thalamocortical pathway and many cortical structures involved in memory consolidation. These studies may help explain retrograde amnesia following seizures.